2021
DOI: 10.1108/ijoem-02-2020-0197
|View full text |Cite
|
Sign up to set email alerts
|

Financial and social efficiency analysis of Islamic microfinance institutions

Abstract: PurposeThe purpose of this paper was to investigate the impact of credit risk-taking on financial and social efficiency and examine the relationship between credit risk, capital structure and efficiency in the context of Islamic microfinance institutions (MFIs) compared to their conventional counterparts.Design/methodology/approachThe stochastic frontier approach was used to estimate the financial and social efficiency scores, in a first step. In a second step, the impact of risk-taking on efficiency was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
0
3
0
1
Order By: Relevance
“…Similarly, the business concepts of microfinance (e.g. Chipeta and Deressa, 2016; Fersi and Boujelbène, 2021) and FDI arrangements (e.g. Hakimi and Hamdi, 2017; Bhasin and Kapoor, 2021) are so unique to the emerging markets and have led to a plethora of innovations.…”
Section: Suitabilitymentioning
confidence: 99%
“…Similarly, the business concepts of microfinance (e.g. Chipeta and Deressa, 2016; Fersi and Boujelbène, 2021) and FDI arrangements (e.g. Hakimi and Hamdi, 2017; Bhasin and Kapoor, 2021) are so unique to the emerging markets and have led to a plethora of innovations.…”
Section: Suitabilitymentioning
confidence: 99%
“…Additionally, results also revealed that MFIs with more assets, staff and more clients are able to better achieve their financial and social goals. These revealed results are in accordance with those concluded by Fersi and Boujelbène (2021), who empirically showed that larger MFIs, are more likely to have higher financial and social efficiencies. Moreover, regardless of age and size, the average efficiency scores for MFIs are low.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bu çalışmalarda İ� MFK'ların performansı kimi zaman finansal açıdan kimi zaman da sosyal açıdan değerlendirilmektedir (Purwanto et al, 2020;Siti-Nabiha & Norfarah, 2020;Siti-Nabiha & Siti-Nazariah, 2022). İ� MFK'ların performansını, konvansiyonel MFK'larla karşılaştıran pek çok çalışma bulunmaktadır (Ashraf et al, 2014;Widiarto & Emrouznejad, 2015;İbrahim et al, 2018;Suzuki et al, 2018;Al-Awlaqi & Aamer, 2019;Berguiga et al, 2020;Wasiaturrahma et al, 2020;Fersi & Bougelbene, 2021;)…”
Section: İslami Mikrofinans Kuruluşları Ortaya çıKışıunclassified